Analisis Tingkat Kepuasan Pengguna Sistem Informasi Akademik Menggunakan Metode PIECES - Laday, Ravie Kurnia; Achmad, Yunita Fauzia (Universitas Lembah Dempo, 2022)
Academic information system is a management information system that manages and regulates various activities within an institute or college. In the operation of the academic information system requires several interconnected components such as software hadware and operators. The academic information system at the Institut Sains dan Teknologi Al-Kamal (ISTA) was built by utilizing information technology and to maintain the quality of the system, an end user satisfaction assessment is needed which aims to determine whether the quality of the system has met the needs of the user or not yet. One of the system evaluation methods used is the PIECES Framework. The PIECES Framework is a system evaluation framework related to performance, information, economics, control, efficiency, and service. The study aims to measure the level of user satisfaction with the academic information system, and to determine the strengths and weaknesses of the academic information system. This study consists of several stages and one of the stages is the data collection process using a questionnaire technique, where the sample used is twenty five users, namely students of the Institut Sains dan Teknologi Al-Kamal. The result of this study are in the form of a user satisfaction index, which is 3.52 where this value states the level of user satisfaction with academic information system and is in accordance with user needs.